HUBUNGAN ANTARA PANTANG MAKANAN IBU NIFAS DENGAN KECEPATAN PENYEMBUHAN LUKA PERINEUM - Hardianty, Dian; Sari, Dewi Kartika; Mualimah, Miftakhul (Jurnal Mahasiswa Kesehatan, 2021)
ABSTRACT Tabu is a prohibition to consume a particular food in a pasticular culture.Based on prelimary study at Puskesmas Nosarara Palu district of 22 patients who gave birth to delayed wound healing as many as 15 people. The purpose of this research isto know relationship between food abstinence puerperal women with perineal wound healing rate in village region Puskesmas Nosarara Palu district 2020. The research design used analytic correlation with approach cross sectional. The population in this study were all postpartum mother who gave birth to normal has perineal woundwith engineering total sampling retrived sample of 35 people. Instrument of this research are observation sheet wound healing and questionnaires. The results of this study analyzed by sperman rank. The result showed most of respodents(57,6%)didn’t food abstinence. Most of respondentas (51,4%)  have perineal normal speed wound healing. Based on bivariat analyze for relationship between food abstinence puerperal women with perineal wound healing rate with α = 0,05 obtained p value = 0,002, r = 0,571sop value<  α  means H0 rejecteddan H1accepted. Conclusion is this research there are relationship between betweenfood abstinence puerperal women with perineal wound healing rate. Based on the result of the research for clinical should improve services including healt education on the impact of abstinence eat and provide oversight regarding nutrition postpartum mother. Key word: postpartum, abstinence food, perineal wound